Angyomatous vocal polypus: a complete spontaneous regression - Lourenço, Edmir Américo; Costa, Luís Henrique Chechinato (São Paulo Medical Journal, 1996)
The authors describe a male patient who had malignant lymphoma seven years ago which remitted with chemotherapy.Two years ago he developed dysphonia. An unilateral, pediculate smooth red lesion on the right vocal fold was later discovered. Even without benefit of medicamentosus treatment, the patient refused surgery. In a reevaluation using rigid telescopy of the larynx two years later, the lesion had disappeared, completely and spontaneously. As there are no existing publications on this topic, this case report is an alert that surgery should be recommended with extreme caution in this type of vocal disease.